Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1894)
Demorest's Family Magazine, September 1894. Vol. 30, No. 11 -- Spongers and Sponging in Florida -- A Day Among the Shakers -- Submarine Lights -- Fads, Hobbies, and Recreations of Famous People -- The Road to Fame or Fortune -- Society Fads -- A Flash Acquaintance -- Among the Palmettos -- In a Glass-House -- The Resurrection of Hanna Higgs -- Waring's Tip -- Home Art and Home Comfort: Fans in Decoration -- Our Girls: A Castle in the Air -- Sanitarian: Corpulence Considered as a Disease -- Chat -- A Failure in Business -- Household: Summer Guests and Their Entertainment -- What Women Are Doing -- Puzzles -- The World's Progress -- Mirror of Fashions -- Woman's Relation of Temperance -- The Most Effective Missionary Enterprise -- Correspondence Club -- Gleanings
New York Illustrated News
Mme Demorest's Mirror of Fashions
Digitized from original print, Valdosta State University Archives and Special Collections, February 3, 2017.
Keywords: Demorest's Family Magazine; New York Illustrated News; Mme Demorest's Mirror of Fashions; Magazine; Illustrated Periodicals; Catalogue; Dressmaking; Needlework; Fashion; Homemaking; Travel; Women; Children; Women's History; Social History; United States; 1800s; 1894; 19th Century; Sponging